MCSE guide to designing a Microsoft Windows server 2003 active directory and network infrastructure - Barber, Brian (Course Technology/Thomson Learning, 2005)
Students will master the objectives for the new MCSE exam # 79-297 using an approach created specifically for the classroom. Their learning will be enhanced with extensive end-of-chapter exercises and hands-on projects